THE EFFECTIVENESS OF THE WAKALAH ACCOUNT ON WOMEN GROUP SPECIFIC LOAN SAVINGS FROM THE NATIONAL PROGRAM FOR SHARIA-BASED COMMUNITY E - Arifin, Zarul (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research is based on the National Program for Community Empowerment in Semparuk sub-district, which was previously conventional, has now switched to Sharia using the wakalah contract. This study aims to determine the effectiveness and analysis of Islamic law on the wakalah contract in the Sharia-based National Community Empowerment Program in the Semparuk Activity Management Unit. The type of this research is field research, using a descriptive qualitative approach. The collection techniques used in this study were interviews, documentation based on primary sources, namely the management of the Semparuk Activities Management Unit and groups of women (customers) who borrowed from the Sharia-based National Community Empowerment Program. Based on the research results, it is concluded that the effectiveness of the National Community Empowerment Program is good. Semparuk Activities Management Unit has carried out business activities based on sharia principles or Islamic legal principles which are regulated in the fatwas of the Indonesian Ulema Council such as the principles of justice and balance, and do not contain gharar, maysir, usury, zalim and haram objects.